Intellectual disability nursing : an oral history project - Gates, Bob; Griffiths, Colin; Atherton, Helen L.; McAnelly, Su; Keenan, Paul; Fleming, Sandra; Doyle, Carmel; Cleary, Michelle; Sutton, Paul (Emerald points., 2020)
This book presents oral histories of 31 long-serving intellectual disability nurses' careers and seeks to understand their experiences of and motives for working in this field. These recordings form a unique collection in the Royal College of Nursing's archives and will help put into perspective the current UK nursing workforce crisis.